2011
DOI: 10.1128/ec.00208-10
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of the Cellulase Transcription Factors XYR1, ACE2, and ACE1 in Trichoderma reesei Strains Producing High and Low Levels of Cellulase

Abstract: Due to its capacity to produce large amounts of cellulases, Trichoderma reesei is increasingly being investigated for second-generation biofuel production from lignocellulosic biomass. The induction mechanisms of T. reesei cellulases have been described recently, but the regulation of the genes involved in their transcription has not been studied thoroughly. Here we report the regulation of expression of the two activator genes xyr1 and ace2, and the corepressor gene ace1, during the induction of cellulase bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
129
1
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 147 publications
(144 citation statements)
references
References 40 publications
5
129
1
9
Order By: Relevance
“…XYR1 is an essential transcription factor of cellulase gene expression not only on cellulose but also on lactose (43,(62)(63)(64). It was shown that XYR1 binds to one of its target promoters (xyn1) not only under inducing conditions but also under repressing conditions (44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…XYR1 is an essential transcription factor of cellulase gene expression not only on cellulose but also on lactose (43,(62)(63)(64). It was shown that XYR1 binds to one of its target promoters (xyn1) not only under inducing conditions but also under repressing conditions (44).…”
Section: Discussionmentioning
confidence: 99%
“…Transcription of ace1, ace2, and xyr1 is induced upon growth on lactose. While ace1 is carbon catabolite repressed, the carbon catabolite repressor CRE1 is necessary for full induction of ace2 and xyr1 (43). Analysis of the genome of T. reesei revealed, surprisingly, that this industrial workhorse has an unexpectedly small number of genes for cellulases, hemicellulases, and pectinases (37).…”
mentioning
confidence: 99%
“…This protein is a homolog to XlnR of A. niger (1010) and has been demonstrated to act as an activator of xylanase and cellulase genes (1008,1009,1011). A third Zn(II) 2 Cys 6 TF has been studied in T. reesei (1012).…”
Section: The Zn(ii) 2 Cys 6 -Type Fungal Binuclear Cluster Familymentioning
confidence: 99%
“…The carbon catabolite repressor gene cre1 was described in T. reesei; it recognizes the AGGGG motif, similar to CREA of A. nidulans (1018,1019). CRE1 (TR_120117, TA_301116, and TV_149403) is essential for the control of carbon catabolite repression by glucose and is of utmost importance to industrial enzyme production, especially with respect to cellulases (1009). A truncation of CRE1 is the major defect of the T. reesei strain RutC30, the parental strain of numerous industrial production strains (1020).…”
Section: C2h2 Zinc Finger Transcription Factorsmentioning
confidence: 99%
“…The highest amount of cellulases reported for a certain strain was the industrial strain CL487. Interestingly, we could recently show that in contrast to the published genealogy of this mutant, the strain is in fact a progeny of RUT-C30 since it shares a number of mutations also found in RUT-C30 (Portnoy et al, 2011). Since most of the cellulase genes are regulated in a coordinated way, only the relative ratio of their expression differs in higher production mutants (Foreman et al, 2003).…”
Section: Cellulase Production and Engineeringmentioning
confidence: 82%